2021
DOI: 10.23918/ijsses.v8i4p298
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Ethical Values and Norms-Variances based on Education and Gender on Justification of Violence

Abstract: Ethics reflect beliefs about what is right, what is wrong, what is just, what is unjust, what is good, and what is bad in terms of a person's behavior. Do ethical values differ based on gender? Do the ethical values differ based on education and age? The objective of this paper is to explore variances based on the factors of gender and education on the three ethical variables namely, 'Justifiable a man beating his wife', 'Justifiable Parents beating their children', and Justifiable violence against others'. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Overall, the findings of the current study suggest that the effectiveness of the formal education system in providing necessary skills and training is viewed differently by male and female respondents in Iraq. These findings are consistent with the previous study by Kavlu & Begum (2022) where a significant variance was found across different gender, ages, and education on the justifiability of parents beating children, taking the Iraq's data.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the findings of the current study suggest that the effectiveness of the formal education system in providing necessary skills and training is viewed differently by male and female respondents in Iraq. These findings are consistent with the previous study by Kavlu & Begum (2022) where a significant variance was found across different gender, ages, and education on the justifiability of parents beating children, taking the Iraq's data.…”
Section: Discussionsupporting
confidence: 92%
“…Due to underreporting, the actual rate of violence is unknown (Giacaman, Shannon, Saab, Arya, & Boyce, 2007;Inter-Parliamentary Union, 2007) and cannot be determined. For most countries, there are no long-term statistics on violent discipline against children.…”
Section: Introductionmentioning
confidence: 99%